High Strength Anhydrite Cement Based on Lime Mud From Water Treatment Process: One Step Synthesis in Water Environment, Characterization and Technological Parameters - Maksim Kamarou; Hongbin Tan; Dmitry Moskovskikh; Natallia Kulinich; Xiaoling Ma; Feihua Yang; Evgenii Beletskii; Elena Alekseeva; Sergey Yudin; Valentin Romanovski (Engineering Reports)
ABSTRACT In the process of water treatment from surface water sources, lime mud as waste is formed. This waste contains CaO, Ca(OH)2, and CaCO3. The article proposes a comprehensive method for processing lime mud into high‐strength anhydrite cement. The method involves the interaction of lime mud with waste sulfuric acid from the production of polymer fibers using a structure‐controlled method in the (CaO·Ca(OH)2·CaCO3)—H2SO4—H2O system at a temperature of 40°C. X‐ray diffraction analysis showed the presence of CaSO4 and CaSO4·0.62H2O phases with a purity of 99.8%. The structure‐controlled method makes it possible to control the formation and growth of calcium sulfate crystals of the required shape and size, due to which it is possible to obtain anhydrite cement with desired properties. Combined grinding of synthetic anhydrite with activator additives makes it possible to obtain anhydrite cement with a strength of up to 28.5 MPa.